2019
DOI: 10.2174/1573405614666181018123251
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Cartilage from Knee Joint Magnetic Resonance Images and Quantitative Assessment to Study the Effect of Age, Gender and Body Mass Index (BMI) in Progressive Osteoarthritis (OA)

Abstract: Background: Osteoarthritis (OA) is a degenerative disease of joint cartilage affecting the elderly people around the world. Visualization and quantification of cartilage is very much essential for the assessment of OA and rehabilitation of the affected people. Magnetic Resonance Imaging (MRI) is the most widely used imaging modality in the treatment of knee joint diseases. But there are many challenges in proper visualization and quantification of articular cartilage using MRI. Volume rendering and 3D visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…In the previous studies, a lot of evidence have shown that gender and age are closely related to the occurrence and progression of osteoarthritis. [ 14 ] Furthermore, the relationship between BMI and osteoarthritis has been confirmed in previous literature. Wolfe and Lane have shown that female patients with high body mass index are more likely to suffer from osteoarthritis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the previous studies, a lot of evidence have shown that gender and age are closely related to the occurrence and progression of osteoarthritis. [ 14 ] Furthermore, the relationship between BMI and osteoarthritis has been confirmed in previous literature. Wolfe and Lane have shown that female patients with high body mass index are more likely to suffer from osteoarthritis.…”
Section: Discussionsupporting
confidence: 62%
“…In the previous studies, a lot of evidence have shown that gender and age are closely related to the occurrence and progression of osteoarthritis [14] . Furthermore, the relationship between BMI and osteoarthritis has been confirmed in previous literature.…”
Section: Discussionsupporting
confidence: 55%
“…In Asia, osteoarthritis of the knee is predominant, which may be related to different living habits and living environments. The epidemiological findings show that the peak prevalence of osteoarthritis in men and women can reach 24.7% and 54.6%, respectively, which is one of the diseases that greatly endanger the health of the elderly and seriously affect their quality of life [ 7 ]. With the rapid development of social economy, people's social lifestyle has changed, and the concept of health and medical model is also changing.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms, including pain, stiffness and walking disability can increase to the point to deteriorate life quality, leading in some cases to depression [ 5 ]. The pathology is prevalent in the obese female population, and correlates with knee diameter [ 6 , 7 , 8 , 9 ]. Disease frequency and severity increase with increasing age [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%